Итоги интродукции петрофитных и псаммофитных видов флоры юго-востока Украины в искусственных фитоценозах - Назаренко, А.С. (Промышленная ботаника, 2013)
Оцінено успішність інтродукції 196 видів флори південного сходу України при вирощуванні у штучних рослинних угрупованнях. Встановлено, що успішність інтродукції досліджених видів залежить від життєвої форми, екологічної амплітуди за відношенням до субстрату, розміру ареалу, раритетності. Види з середньою та низькою успішністю інтродукції потребують спеціальних заходів для підтримання інтродукційних популяцій. The introduction success of 196 species belonging to the flora of the south-eastern Ukraine was evaluated in the course of growing in man-made plant communities. The study has shown that introduction success depends on the plant biomorph, ecological amplitude as far as the substrate preference is concerned, the size of the species distribution range and its rarity. The species characterized by an average and low introduction success require special measures for maintenance of introduced populations.